2022
DOI: 10.1101/2022.03.23.485424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural and cognitive correlates of performance in dynamic multi-modal settings

Abstract: The endeavour to understand human cognition has largely relied upon investigation of task-related brain activity. However, resting-state brain activity can also offer insights into individual information processing and performance capabilities. Previous research has identified electroencephalographic resting-state characteristics (most prominently: the individual alpha frequency; IAF) that predict cognitive function. However, it has largely overlooked a second component of electrophysiological signals: aperiod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…The effect of differing levels of 1/ f slope on, for instance, beta power and behavioural performance likely reflect more nuanced inter-individual differences in information processing capacities (Dziego et al, 2022; Immink, Cross et al, 2021; Thuwal, Banerjee, & Roy, 2021), which may explain behavioural gains that are otherwise related to the manifestation of oscillatory activity (e.g., Kepinska et al, 2017). For example, here we observed that a decrease in beta power predicted better behavioural performance for flexible rules, while the inverse was seen for fixed word order rules.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of differing levels of 1/ f slope on, for instance, beta power and behavioural performance likely reflect more nuanced inter-individual differences in information processing capacities (Dziego et al, 2022; Immink, Cross et al, 2021; Thuwal, Banerjee, & Roy, 2021), which may explain behavioural gains that are otherwise related to the manifestation of oscillatory activity (e.g., Kepinska et al, 2017). For example, here we observed that a decrease in beta power predicted better behavioural performance for flexible rules, while the inverse was seen for fixed word order rules.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, whilst IAF influenced N400 amplitudes, we did not detect any effects relating to the 1/f aperiodic slope. Although we investigated 1/f as a between-subjects (trait-like) measure, in line with prior research (e.g., Demuru & Fraschini, 2020;Dziego et al, 2023;McSweeney et al, 2021;, the 1/f slope also shows state-like changes and has been linked with norepinephrine activity and phasic changes in neural gain (Pertermann et al, 2019;Rosenblum, 2023). Consequently, future research may benefit from examining 1/f on a trial-by-trial basis to determine whether changes relating to prediction may be more transient.…”
Section: Individual Alpha Frequency (Iaf) Modulates Predictive Proces...mentioning
confidence: 81%
“…Despite periodic oscillatory components such as IAF traditionally being linked to cognitive processing, the importance of considering the aperiodic noise-like activity (particularly the 1/f slope of the distribution) that underlies the EEG spectra has been recently emphasised in the literature (Cross et al, 2022;Demuru & Fraschini, 2020;Dziego et al, 2023;Immink et al, 2021;Merkin et al, 2023;Ouyang et al, 2020;. Although prior literature recommends controlling for this activity to directly probe periodic (i.e., oscillatory) patterns (Donoghue et al, 2020), the 1/f component has been shown to predict information processing speeds (Ouyang et al, 2020), and to mediate the relationship between age and cognitive functioning (Pathania et al, 2022;, suggesting that it may be relevant for cognition.…”
Section: The Influence Of Individual Neural Factors On Predictionmentioning
confidence: 99%
“…Individual alpha frequency (IAF) is associated with memory (Lebedev, 1994), language (Bornkessel et al, 2004;Bornkessel-Schlesewsky et al, 2015), attention (Angelakis et al, 2004, Klimesch et al, 1993, general cognitive ability (g-factor intelligence; Grandy et al, 2013a, Zakharov et al, 2020, and has recently been shown to modulate sleep-related memory consolidation (Chatburn et al, 2021;Cross et al, 2020b). Specifically, a growing body of work shows that IAF is a more sensitive measure of individual cognitive performance than behavioural measures alone in studying language comprehension (Bornkessel et al, 2004;Bornkessel-Schlesewsky et al, 2015;Kurthen et al, 2020), as well as in naturalistic paradigms of cognition (Dziego et al, 2022) The functional significance of IAF as a robust marker of information processing makes it a potentially informative metric for examining individual differences in L2 learning, as it is advantaged by its stable, trait-like characteristics (Posthuma et al, 2001) and test-retest reliability in samples of healthy individuals (Grandy et al, 2013b).…”
Section: Individual Alpha Frequency As a Neurophysiological Proxy For...mentioning
confidence: 99%